Estimating Effect of Subsidies on SME Performance and Growth - Čechová, Gabriela; Janíčko, Martin, 1983-; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
The goal of this thesis is to explore the impact of R&D subsidy on firms’ performance. The companies’ employment, sales and productivity measures are observed on unique Czech dataset of firm level data for the period 2013 – 2018. The causal effect analysis is applied in form of difference-in-differences model estimation combined with CEM matching method (coarsened exact matching). The methodology is further applied to observe the post treatment years separately and to provide insights on role of firm size. The results indicate positive effect on employment and productivity in both short term and medium term. When observing the yearly post treatment effect, the estimates for first two years are lacking significance, however the third and fourth year estimates show positive and increasing effect on both sales and productivity of the companies. The positive effects of subsidy on productivity performance indicator are also found for the cases of micro and small firms compared to the large enterprises. The findings support (although with reservations) the hypothesis about positive effect of subsidy on firm’s performance, especially for micro and small firms.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses